(untitled) (Journal of Economic Research & Business Administration, 2017)
The article is devoted to research of dynamics of economy’s development of the Republic of Kazakhstan for the last two years. In particular, the deterioration was observed in key macroeconomic indicators in 2015. Real growth of gross domestic product decreased by 2.9% in comparison with the previous period. Also there is decline in prices for oil and metals on the world market, in industrial production and retail trade in Kazakhstan, in foreign trade turnover and crediting of economy of the Republic of Kazakhstan, in international reserves and foreign exchange assets of the National Bank. The opposite trend is observed in the agricultural sector and in the volume of deposits in the banking system. In its turn, investment activity of economic entities has not changed. In 2016, the global economy remains in low growth but in the first half of the year one has seen positive changes in the prices of oil and metals. The article also noted risks, which are able to resume crisis trends (instability of world commodity prices, the change in the monetary policy of the United States, unfavorable geopolitical situation). On the basis of analyzed data it was noted that in the medium term, global growth will be profitable.